2017
DOI: 10.1097/aog.0000000000002035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Myomectomy Practice After the U.S. Food and Drug Administration Safety Communication on Power Morcellation

Abstract: The FDA safety communication on power morcellation was associated with an 11% absolute increase in the use of abdominal myomectomy. Although morbidity is consistently higher after abdominal as compared with laparoscopic myomectomy, the increased reliance on abdominal myomectomy post-FDA did not result in clinically significant changes in morbidity in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 15 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…The U.S. Food and Drug Administration (FDA) published its initial safety communication, which reported that the risk of occult ULMS after morcellation was 0.2% or 1 in 498 patients. [ 9 ] Rodriguez et al recently reported that the prevalence of occult ULMS in presumed morcellation cases was 0.14% or 1 in 714 patients. [ 10 ] Cao et al reported that the prevalence of occulted ULMS was 0.11% (29/26643) and that of morcellation was 0.02%.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Food and Drug Administration (FDA) published its initial safety communication, which reported that the risk of occult ULMS after morcellation was 0.2% or 1 in 498 patients. [ 9 ] Rodriguez et al recently reported that the prevalence of occult ULMS in presumed morcellation cases was 0.14% or 1 in 714 patients. [ 10 ] Cao et al reported that the prevalence of occulted ULMS was 0.11% (29/26643) and that of morcellation was 0.02%.…”
Section: Discussionmentioning
confidence: 99%
“…The number of laparoscopic procedures has decreased in favor of laparotomy, since the Food and Drug Administrations (FDA) decided to discourage power morcellation [ 1 5 ] This decision was based on the occurrence of unexpected uterine (leiomyo)sarcoma during hysterectomy or myomectomy for presumed benign fibroids. It was calculated by the FDA that this risk is as high as 1 in 498 for uterine leiomyosarcoma (ULMS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analgesics: N (%) 18 (43.9) 52 (54.7) NS SD standard deviation, NS non-significant, HB hemoglobin, UTI urinary tract infection [18][19][20][21][22][23]. Morcellation was not used in the present study.…”
Section: Discussionmentioning
confidence: 99%